2020
DOI: 10.1101/2020.05.29.20086645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and Outcomes of COVID-19 Patients in New York City’s Public Hospital System

Abstract: Background New York City (NYC) has borne the greatest burden of COVID-19 in the United States, but information about characteristics and outcomes of racially/ethnically diverse individuals tested and hospitalized for COVID-19 remains limited. In this case series, we describe characteristics and outcomes of patients tested for and hospitalized with COVID-19 in New York City's public hospital system. Methods We reviewed the electronic health records of all patients who received a SARS-CoV-2 test between March 5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 14 publications
5
37
0
3
Order By: Relevance
“…Significant racial disparities among populations affected by COVID-19 have recently made headlines. Some sources have also cited SARS-CoV-2 as a possible cause of stroke [1]. Nationally, Hispanics and Blacks are disproportionately represented among laboratory-confirmed COVID-19 cases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Significant racial disparities among populations affected by COVID-19 have recently made headlines. Some sources have also cited SARS-CoV-2 as a possible cause of stroke [1]. Nationally, Hispanics and Blacks are disproportionately represented among laboratory-confirmed COVID-19 cases [2].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of COPD among patients with COVID-19 was summarised in a systematic review of 15 studies that had been published by 24th March 2020 involving 2473 patients with confirmed COVID-19, mainly from China; a prevalence of 2% (95% CI 1-3%) was reported (figure 3) [98]. A similar prevalence (3%), was found in a more recent report assessing 13 442 patients diagnosed with COVID-19 after an emergency department visit or admission in New York (NY, USA) [101] and a report of 1099 unselected patients from China (1%, 95% CI 0.6−1.9%) [100]. To explain the lower than anticipated observed prevalence of COPD among patients with COVID-19, it has been proposed that either the disease or its treatment may reduce the risk of infection [108].…”
Section: Epidemiology and Clinical Outcomes Of Covid-19 In Copd Patientsmentioning
confidence: 75%
“…Prevalence % (95% CI) ALQAHTANI [98] ARGENZIANO [99] GUAN [100] MARCELLO [101] Hospitalised patients ARGENZIANO [99] BARTOLETTI [102] DOCHERTY [103] MARCELLO [101] PARANJPE [104] RICHARDSON [105] Critically ill patients ARGENZIANO [99] CUMMINGS [ Consistently, the prevalence of COPD rises further among patients suffering from more critical or lethal COVID-19 disease. A series of 257 critically ill patients admitted to the intensive care unit with COVID-19 in New York revealed a much higher prevalence of COPD (9%) and current or former smokers (33%) [106].…”
Section: All Diagnosedmentioning
confidence: 97%
“…In initial reports, based primarily on Chinese studies, the median age of patients varied between 47 and 56 years and a majority were males (53·4–73%) [18,80]. Subsequently, studies from several countries have reported the mean age of COVID‐19 patients, varying from 39 years (Brazil) to 72 years (US) [77,81–84]. For most countries, the average age of patients was >60 years.…”
Section: Covid‐19: Disease Characteristicsmentioning
confidence: 99%